The accuracy of contrast-enhanced computed tomography scans to detect postpartum haemorrhage: an observational study - Yumi Mitsuyama; Yusuke Katayama; Kazuya Oi; Junya Shimazaki; Kazuya Mimura; Masayuki Endo; Takeshi Shimazu (BMC, 2022)
Abstract Introduction Postpartum haemorrhage is a major cause of maternal mortality. Although contrast-enhanced computed tomography (CE-CT) is useful to reveal arterial bleeding, its accuracy in postpartum haemorrhage is unclear. The aim of this study was to evaluate the accuracy of CE-CT scanning in detecting postpartum haemorrhage. Methods This was a retrospective observational study. We included patients with postpartum haemorrhage treated by emergency physicians in collaboration with obstetricians. We calculated the sensitivity, specificity, and positive and negative predictive values for CE-CT scanning to detect arterial bleeding. Results CE-CT scanning was performed in 52 patients, and 31 patients had extravasation. The sensitivity of CE-CT scanning to detect arterial extravasation was 100% (15/15), specificity was 28.6% (2/7), positive predictive value was 75% (15/20), and negative predictive value was 100% (2/2). Conclusion We showed the sensitivity of CE-CT scanning to detect arterial extravasation in patients with postpartum haemorrhage to be 100%.